AAssociation between migraine and ischaemic stroke in Prof. Dr. Margono Soekarjo Hospital, Purwokerto, Indonesia - Yahdiyani Razanah (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
Headache especially the migraine type has been correlated with various disease, such as stroke. There are some controversies in studies that reported association between migraine and ischaemic stroke. Thus, study that investigate the association between migrain – stroke andalso identify stroke risk factor are needed. Study showed there is no statistically significant relationship between migraine and ischaemic stroke in RSUD Prof. Dr. Margono Soekarjo Purwokerto (p=0,235). Analysis of confounding variables such as hypertension, smoking, diabetes, obesity, alcohol consumption, and oral contraceptive shows that hypertension is a predictor for stroke.